2021
DOI: 10.1002/pst.2158
|View full text |Cite
|
Sign up to set email alerts
|

Estimands for overall survival in clinical trials with treatment switching in oncology

Abstract: An addendum of the ICH E9 guideline on Statistical Principles for Clinical Trials was released in November 2019 introducing the estimand framework. This new framework aims to align trial objectives and statistical analyses by requiring a precise definition of the inferential quantity of interest, that is, the estimand. This definition explicitly accounts for intercurrent events, such as switching to new anticancer therapies for the analysis of overall survival (OS), the gold standard in oncology. Traditionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…2 The recently released ICH-E9(R1) addendum 6 defines an estimand in terms of five attributes (treatment, population, variable, intercurrent events and population-level summary), without linking the issues arising in clinical trials to specific models for the processes in question. Numerous researchers and working groups have proposed estimands and guidelines for specific settings involving competing risks, 2,7-10 recurrent and terminal events, [11][12][13] introduction of rescue therapies, 14 or treatment switching; 15,16 see also Casey et al 17 and Stensrud and Dukes. 18 Much of the discussion regarding challenges in conceptualizing and specifying treatment effects often lacks detail concerning models and assumptions, which makes interpretation of the recommended estimands difficult.…”
Section: Overviewmentioning
confidence: 99%
“…2 The recently released ICH-E9(R1) addendum 6 defines an estimand in terms of five attributes (treatment, population, variable, intercurrent events and population-level summary), without linking the issues arising in clinical trials to specific models for the processes in question. Numerous researchers and working groups have proposed estimands and guidelines for specific settings involving competing risks, 2,7-10 recurrent and terminal events, [11][12][13] introduction of rescue therapies, 14 or treatment switching; 15,16 see also Casey et al 17 and Stensrud and Dukes. 18 Much of the discussion regarding challenges in conceptualizing and specifying treatment effects often lacks detail concerning models and assumptions, which makes interpretation of the recommended estimands difficult.…”
Section: Overviewmentioning
confidence: 99%
“…A subject switching treat ment in an oncology trial as an intercurrent event (ICE) for which the clinical question of interest must be clear and appropriate strategies for addressing this event be applied. Helpfully, Manitz et al 17 has recently reported an estimand framework for OS in oncology trials with treatment switching.…”
Section: Endpoints Selectionmentioning
confidence: 99%
“…Ways to define estimands and make treatment comparisons in the presence of intercurrent events have received a great deal of attention in recent years (Rufibach, 2019). Numerous researchers and working groups have proposed estimands and guidelines for specific settings involving competing risks (Rufibach, 2019;Stensrud et al, 2020;Young et al, 2020;Nevo and Gorfine, 2021;Poythress et al, 2020), recurrent and terminal events (Andersen et al, 2019;Schmidli et al, 2021;Wei et al, 2021), introduction of rescue therapies (Ster et al, 2020) or treatment switching (Watkins et al, 2013;Manitz et al, 2022); see also Casey et al (2021) and Stensrud and Dukes (2022).…”
Section: Introduction 1overviewmentioning
confidence: 99%